Papel da angiotensina -(1-7) na migração de células mononucleares - Isabella Zaidan Moreira (2019)
The resolution of inflammation is an active process highly regulated and characterized by key events such as neutrophil apoptosis followed by its removal by macrophages - a process named efferocytosis. The nonphlogistic migration of macrophages contributes greatly to the clearance of apoptotic cells and consequently resolution of inflammation. It has been shown that Angiotensin-(1-7), a metabolite of the Renin-Angiotensin system, has proresolving actions, such as induction of neutrophil apoptosis and removal of apoptotic bodies by efferocytosis. In this study, we have investigated the role of Ang-(1-7) to inducing the migration of human (monocytes) and murine macrophages (RAW 264.7 and Bone Marrow Derived Macrophages - BMDMs) and the involvement of the MEK/ERK pathway and the receptors Mas and CCR2 in this process, by applying in vitro and in vivo studies. Ang-(1-7) induced migration of human monocytes and murine macrophages in transwell plates. By using selective pharmacological antagonists of CCR2 (RS504393) and Mas (A779) receptors in RAW264.7 macrophages as well as BMDMs from CCR2-/- mice, it was found that Ang-(1-7)-induced migration was dependent on Mas and CCR2. Inhibition of the MEK/ERK pathway, which is an important pathway for mononuclear cell migration, using two different inhibitors (Selumetinib and U0126), prevented Ang-(1-7)-induced chemotaxis of murine macrophages. In BALB/c mice, intra-articular and intrapleural injection of Ang-(1-7) induced an influx of mononuclear cells into the respective cavities, associated with increased CCL2 levels. The leukocytes recruited to the pleural cavity after Ang-(1-7) injection were mainly composed by monocytes (Ly6C+/F4/80-) as ascertained by flow cytometry. Akin to the in vitro data, pretreatment of mice using antagonists of CCR2 and MasR (RS504393 or A779), or the inhibition of the MEK/ERK pathway with U0126, compromised the mononuclear cell migration to the pleural cavity after Ang(1-7) injection. We also evaluated the effect of A779 on natural resolution of LPSinduced pleurisy and we found that inhibition of MasR in curse of the LPSinflammation hampers the spontaneous resolution that occurs at 48h time point, characterizing a compromised inflammation resolution. Finally, by using WT and MAS-/- mice, we also have evaluated the role of MasR during LPS-induced inflammation. Our results show that pleurisy was exacerbated in MasR deficient animals (marked by higher numbers of neutrophils at the peak of inflammation - 8h), reinforcing the participation of Ang-(1-7)/MasR axis during resolution of inflammation. Taken together, our results show that Ang-(1-7) is able to promote mononuclear cells recruitment in a manner dependent on the receptors Mas and CCR2 and of the MEK/ERK1/2 pathway. In addition to the Ang-(1-7)-inducing properties of apoptosis and efferocytosis, the no redundant Ang-(1-7)-inducing effect on mononuclear cell recruitment shown here, may contribute to the proresolving properties of this peptide.